Endovascular Graft Infection by Neisseria meningitidis: A Rare but Fatal Infection - Lopez-Marco, Ana; Das, Satya; Serafino-Wani, Robert; Selvakumar, Sadasivam; Adams, Benjamin; Oo, Aung (AORTA, 2020)
Endovascular graft infection is a rare but challenging complication that requires a tailored approach to remove the infected graft and restore the arterial circulation combined with long-term antibiotic therapy. We present a case surgically treated with explant of the graft and reconstruction of the thoracoabdominal aorta. Microbiological investigation revealed growth of Neisseria meningitidis, which is extremely rare in this location, and to our knowledge, has not been previously published in the literature.
Keywords: infrarenal aneurysm; EVAR; infection; thoracoabdominal; meningococcal disease